APPLICATION OF CHROME-LEARING PUCKS IN PRODUCTION OF POWDER-LIKE SPECIAL STEELS - Grigorev , Stanislaw; Kirichenko , Alexis; Volyar , Roman; Zinchenko , Helena (Scientific Journal "Metallurgy", 2020)
The Ukrainian and foreign experience in the production of ferrosilicoaluminium differing in the type of aluminosilicate raw materials: bauxite agglomerate, ash of thermal power plants, coal processing waste is analyzed. The results of laboratory studies in the conditions of state enterprise “UkrNIIspetsstal” are given for the technological features of the production of ferrosilicoaluminum using secondary materials, in particular aluminum slag (fraction < 7 mm, aluminum content 22-27%) and ferrosilicon screenings (fraction < 6 mm) as charge materials. The influence of the ratio of aluminum slag mass (contains 20% aluminum) to ferrosilicon (grade ФС65) mass in the charge on the technological parameters of smelting ferrosilicoaluminum is shown: metal yield, aluminum content in the alloy, degree of recovery of silicon and aluminum. At that, in the charge the ratio of masses of aluminum slag and ferrosilicon screenings changed from 1.0 to 2.0, the ratio of masses of lime and aluminum slag mass was from 0.25 to 1.0, as well as the quantity of fluorspar changed with mass of given lime (from 5 to 15%). It has been experimentally shown that the production of ferrosilicoaluminum with an aluminum content of more than 10% is possible if the ratio of aluminum slag mass to ferrosilicon screenings mass is maintained at a level of 2.0. The dependences of metal yield, aluminum content in ferrosilicoaluminum, and recovery degree of aluminum on the content of aluminum metal in aluminum slag were analyzed and it was found that with an increase in the metal aluminum content in aluminum slag mass from 20 to 30 wt% its recovery degree increases from 35,6 to 43%, while the aluminum content in ferroaluminum increases from 11.2% to 18%. The optimal ratio between the components of the charge materials for smelting ferrosilicoaluminum is determined: ferrosilicon screenings 23-25%, aluminum slag 48-59%, lime 25-27%, and fluorspar 2-3%, while the recovery degree of silicon is 99-99,6 %. Expense of electric power here made 2580-2620 kW clock on the 1 tone alloy. Thus the degree of aluminium mastering and silicon makes 35-43% and 99,0-99,6% respectively. Finding specify on technologicalness and efficiency of the offered method of receipt of ferrosilicaaluminium